Impaired melanocortin pathway function in prader-willi syndrome gene-magel2 deficient mice - Öncül, Merve; Dilsiz, Pelin; Ateş Öz, Edanur; Ateş, Tayfun; Aklan, İltan; Çelik, Eşref; Sayar Atasoy, Nilüfer; Atasoy, Deniz (Karger, 2018)
[Abstract Not Available]
Keywords: Willi Syndrome Gene; Pathway Function; Magel2